The Effect of Previsit Education in Breast Cancer Patients: A Study of a Shared-decision-making Tool. Issue 3 (March 2016) - Serpico, Victoria; Liepert, Amy E.; Boucher, Kenneth; Fouts, Diane L.; Anderson, Layla; Pell, Joyce; Neumayer, Leigh
To enhance shared decision-making for patients with breast cancer, we developed an evidence-based educational breast cancer video (BCV) providing an overview of breast cancer biology, prognostic indicators, and surgical treatment options while introducing health care choice. By providing patients access to a BCV with information necessary to make informed surgical decisions before seeing a surgeon, we aimed to increase patient participation in the decision-making process, while decreasing distress. Patients with a new diagnosis of breast cancer were provided a link to the BCV. Group 1 participated in online pre- and postvideo questionnaires, with the BCV embedded in between. The questionnaires evaluated self-reported baseline knowledge of breast cancer and perceived distress related to the diagnosis. Changes in self-reported responses were analyzed using the Wilcoxon matched pairs test. Group 2 received a survey collecting demographics, decision-making information, and perceptions of the BCV at the time of clinic visit before meeting the surgeon. Group 1 included 69 subjects with 62 per cent reporting improved knowledge and 30 per cent reporting reduced distress in regard to their breast cancer diagnosis. Group 2 included 87 subjects; 94 to 98 per cent felt the BCV provided information and stimulated thoughts and questions to assist in breast cancer treatment decision-making. The BCV was positively received by participants and feasible to implement into clinical practice. Evidence-based media tools improve knowledge and reduce distress in patients with a new diagnosis of breast cancer as well as contributing to the shared decision-making process.